PENGEMBANGAN MODUL EDUKASI UNTUK PERILAKU KECANDUAN GADGET PADA SISWA MAN 2 KOTA PEKANBARU - Karenzsia yudha; Elni Yakub; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to develop an Educational Module for Gadget Addiction Behavior. The type of research used is Research and Development (R&D). To compile the perfect module, in this study conducted a validation test on 3 fields of expertise, namely material, language and design experts. Data collection techniques in this study used literature review techniques using a validation instrument in the form of a questionnaire using a Likert scale. The results of this study have compiled a learning module with educational material for gadget addiction behavior. The overall module validation test results based on material aspects, language aspects and design aspects show that the assessment obtained an average value of 86.51%, with the category